Innovation in urban real estate: the role of sustainability. Issue 2 (15th April 2019) - Kauko, Tom
Abstract : Purpose: The sustainability agenda has already become widely recognised in real estate analysis. However, two challenges are to overcome before sustainability issues are brought fully into the professional and academic mainstream: first, the provision of sustainability enhancing qualities; and second, to overcome deep-rooted scepticism towards the higher cost element of such qualities (i.e. creating economies of scale). Another potentially related issue is that the notion of innovation is gaining popularity in this field. Innovation-driven change is cyclical and unpredictable, which in turn calls for an explicit evolutionary and complexity perspective. The paper aims to discuss these issues. Design/methodology/approach: Critical literature review. The author's own experience as participant of the discussions and debates is also used. Findings: The conclusions suggest that, in line with evolutionary and complexity principles, innovations exist and emerge within the real estate industry itself, and in fields related to it – and this includes various aspects of promoting sustainability thinking. Research limitations/implications: This contribution uses valuation automata as an example of this argumentation. Practical implications: The concept of complexity refers to emerging qualities found in the evolution of the development of an industry; the practical implication of complexity concerns the capability of managers to react competently in unfamiliar circumstances. Social implications: Thus, innovation in real estate is both economic and socio-cultural. Originality/value: No similar (i.e. theoretically informed) papers on innovation or sustainability in real estate analysis have been written to the best of the author's knowledge.